Integral theorems of deviations for homogeneous Markoff’s chains - Misevičius, E. (Lithuanian Mathematical Journal, 2020)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Мисевичюс. Интегральные теоремы с большими уклонениями для однородных цепей МарковаE. Misevičius. Integralinės didelių nukrypimų homogeninėse Markovo grandinėse teoremos